Analysis of physical properties of facial silicones with different pigmentations submitted to nonthermal plasma treatment and accelerated aging - Paulini, Marcela Borghi [UNESP]; Micheline dos Santos, Daniela [UNESP]; de Moraes Melo Neto, Clóvis Lamartine [UNESP]; Bitencourt, Sandro Basso [UNESP]; Freitas da Silva, Emily Vivianne [UNESP]; Pereira de Caxias, Fernanda [UNESP]; Ribeiro, Rafael Parra [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Sônego, Mariana Vilela [UNESP]; Goiato, Marcelo Coelho [UNESP] (Elsevier, 2020)
Statement of problem: Exposure of silicone prostheses to environmental factors can alter their properties, affecting longevity. However, whether nonthermal plasma (NTP) can prevent these alterations is unclear. Purpose: The purpose of this in vitro study was to evaluate the surface roughness (Ra), sorption, solubility, and color stability (ΔE00) of the MDX4-4210 and A-120 silicones, with and without NTP treatment in accordance with an independent analysis of the use of 2 pigmentations. Material and methods: One hundred sixty specimens were fabricated and distributed into 16 groups (n=10) as per the silicone, pigmentation, and NTP coating. The NTP was applied, and the Ra, sorption, solubility, and ΔE00 were evaluated before and after accelerated aging. ANOVA was used, and the HSD Tukey test was applied (α=.05). Results: NTP generated an increase in roughness after aging, regardless of pigmentation or silicone. A-120 silicone without NTP showed a reduction in roughness after aging, regardless of pigmentation. For sorption and solubility, the bronze pigmentation (for A-120 and MDX4-4210) presented the smallest results after NTP treatment. For MDX4-4210 with pink pigmentation and NTP, sorption decreased and solubility increased. For A-120 with pink pigmentation and NTP, sorption and solubility increased. Sorption was reduced in all situations, except for A-120 with pink pigmentation, which increased. Regardless of the silicone used, solubility was reduced after NTP for bronze pigmentation. For A-120 and MDX4-4210 with pink pigmentation and NTP, the solubility increased. For both pigmentations, the NTP treatment promoted lower color alteration only for the A-120 silicone after accelerated aging (within the acceptability threshold). Conclusions: The NTP protocol of this study, which was applied to facial silicones, generated inconsistent results between the evaluated properties. Therefore, the NTP protocol used does not seem to be ideal for the treatment of silicone surfaces after aging.